1990
DOI: 10.1002/cne.902960403
|View full text |Cite
|
Sign up to set email alerts
|

Organization of geniculocortical projections in turtles: Isoazimuth lamellae in the visual cortex

Abstract: The projection from the dorsal lateral geniculate complex to the visual cortex in Pseudemys and Chrysemys turtles was examined by using the anterograde transport of horseradish peroxidase (HRP) in vitro and the retrograde transport of HRP in vivo. In vitro HRP injections into the lateral forebrain bundle were used to fill geniculocortical axons anterogradely, which were then analyzed in cortical wholemount preparations. Geniculocortical axons gain access to the visual cortex along its entire rostral-caudal ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 30 publications
3
42
1
Order By: Relevance
“…Layer 3 contains basal dendrites of pyramidal cells, corticofugal and local axons, some interneurons and a few deep pyramidal neurons in PCx (Neville and Haberly 2004;Ulinski 1990). Incoming afferents to PCx run through the lateral olfactory tract (LOT; Sosulski et al 2011); those to DCx run through the lateral forebrain bundle (LFB; Mulligan and Ulinski 1990). These input fibers fan out below the pial surface and make en-passant synapses on cortical neurons within the distal 50-100 μm of layer 1 (Haberly and Behan 1983;Smith et al 1980).…”
Section: Vertical Connectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Layer 3 contains basal dendrites of pyramidal cells, corticofugal and local axons, some interneurons and a few deep pyramidal neurons in PCx (Neville and Haberly 2004;Ulinski 1990). Incoming afferents to PCx run through the lateral olfactory tract (LOT; Sosulski et al 2011); those to DCx run through the lateral forebrain bundle (LFB; Mulligan and Ulinski 1990). These input fibers fan out below the pial surface and make en-passant synapses on cortical neurons within the distal 50-100 μm of layer 1 (Haberly and Behan 1983;Smith et al 1980).…”
Section: Vertical Connectivitymentioning
confidence: 99%
“…Although this does not rule out the possibility of some fine-scale topographical mapping of OB projections (e.g., mitral vs. tufted cell projections) (Igarashi et al 2012), it is now accepted that the glomerular clustering of olfactory receptor cells axons in OB is entirely discarded at the level of PCx (Wilson and Sullivan 2011). In DCx, early tracing studies from Ulinski and colleagues suggested that the visual field is projected onto the rostro-caudal axis of DCx in the form of iso-azimuth lamellae covering the naso-temporal dimension of the visual field (Mulligan and Ulinski 1990;Ulinski and Nautiyal 1988). Such a mapping of projections still awaits physiological confirmation and fine thalamocortical projection tracing.…”
Section: Horizontal Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals it survives in both the piriform cortex and the hippocampal formation, often termed "archicortex" or "paleocortex." In turtles (and other reptiles) the three-layered pallium processes not only olfactory but also other sensory information relayed via the thalamus (Desan 1984;Hall and Ebner 1970;Mulligan and Ulinski 1990). There is a broad range of evidence establishing that the more elaborate sixlayered neocortex was derived from the pallium (e.g., Mulligan and Ulinski 1990;Reiner 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In turtles (and other reptiles) the three-layered pallium processes not only olfactory but also other sensory information relayed via the thalamus (Desan 1984;Hall and Ebner 1970;Mulligan and Ulinski 1990). There is a broad range of evidence establishing that the more elaborate sixlayered neocortex was derived from the pallium (e.g., Mulligan and Ulinski 1990;Reiner 2000). In particular, there is evidence that projections onto the dendrites of turtle pyramidal neurons from other cortical and subcortical regions are more laminar and organized than in mammalian pyramidal neurons (Desan 1984;Hall and Ebner 1970;Mulligan and Ulinski 1990;Smith et al 1980).…”
Section: Introductionmentioning
confidence: 99%